2011
DOI: 10.1016/j.ins.2011.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating requirements modeling methods based on user perceptions: A family of experiments

Abstract: Numerous methods and techniques have been proposed for requirements modeling, although very few have had widespread use in practice. One drawback of requirements methods is that they lack proper empirical evaluations. This means that there is a need for evaluation methods that consider both the theoretical and practical aspects of this type of methods and techniques. In this paper, we present a method for evaluating the quality of requirements modeling methods based on user perceptions. The method consists of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 28 publications
(36 reference statements)
0
33
0
Order By: Relevance
“…Dealing with experimental replications has been addressed by the concept of the family of experiments. Although many empirical studies of this type have been applied in the Software Engineering field (e.g., CruzLemus et al [2011]; Abrahão et al [2011]), few families of experiment have been reported in the Web Engineering field (e.g., Abrahão and Poels [2009]). Another issue also appears which is specific to the Web Engineering field: the majority of empirical studies cannot be considered to be methodologically rigorous.…”
Section: Discussionmentioning
confidence: 99%
“…Dealing with experimental replications has been addressed by the concept of the family of experiments. Although many empirical studies of this type have been applied in the Software Engineering field (e.g., CruzLemus et al [2011]; Abrahão et al [2011]), few families of experiment have been reported in the Web Engineering field (e.g., Abrahão and Poels [2009]). Another issue also appears which is specific to the Web Engineering field: the majority of empirical studies cannot be considered to be methodologically rigorous.…”
Section: Discussionmentioning
confidence: 99%
“…How easy is it to construct a model in a language? This concept of understanding is used by, for example, Carvallo & Franch [6] and by Matulevičius & Heymans [13], who measured the number of mistakes made in constructing i* models, and by Abrahao et al, who measured the time needed to build a model [1]. Our concept of understandability is close to the first of these, and we define the understandability of a language construct as the percentage of users that can use a concept correctly.…”
Section: Defining Understandabilitymentioning
confidence: 99%
“…To test the generalizability of these findings, we have replicated the experiment with participants of the REFSQ '14 conference that can be considered experts in GORE languages 1 . We additionally asked the subjects for the perceived understandability of ARMOR concepts in an exit survey.…”
Section: Introductionmentioning
confidence: 99%
“…Participants performed two metacognitive diagrams and the variables used to measuring the user perception with regard to the quality of the notation are based on (Abrahão, Insfran, Carsí, & Genero, 2011;Wohlin et al, 2000): (i) Perceived ease of use. This variable represents a perceptual judgment of the effort required to use M++.…”
Section: Empirical Validation Of M++mentioning
confidence: 99%